Low-level antibiotics in growing-finishing swine rations. - Koch, B.A.; Hines, Robert H. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
The new K-State facilities for growing-finishing swine seemed ideal to re-evaluate various antibiotics as low-level feed additives. The first trial reported here was with the first pigs fed in the new barn. They also were the first farrowed in the new farrowing house, and the first raised in the new nursery. The trials were designed to: (1) compare rations with and without an antibiotic at a low level, (2) various antibiotics and combinations of antibiotics and (3) to determine the need for extra feeder space.
Swine Industry Day 1969 is known as Swine Day, 1969
Keywords: Swine; Antibiotics; Growing-finishing rations; Farrowing